PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ARTICULATE STORYLINE TERHADAP MOTIVASI BELAJAR IPA SISWA KELAS VIII SMP NEGERI 1 BONTONOMPO KAB. GOWA - Nur Maya; Muhammad Nawir; Andi Adam (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to determine the effect of using Articulate Storyline-Based Interactive Learning Media on the Science Learning Motivation of Class VIII Students at SMPN 1 Bontonompo. This type of research is quantitative or experimental research (Pre Experiment) with a One Group Pretest- Posttest design. The population in this study were all students in class VIII E of SMPN 1 Bontonompo which consisted of 6 classes with a total of 176 students. The sample in this research was class VIII E students with a total of 26 students, who were selected through purposive sampling. Data collection techniques in this research are observation, questionnaires and documentation.